Management of Scouting Method Teaching and Its Impact on the Learning Outcomes - Cahya, Ade' Ariska; Rozy, Fakhrur (Journal of Educational Management Research, 2025)
This study investigates the impact of the scouting method on the learning outcomes, specifically on the "Aku Peduli Lingkungan" (I Care About the Environment) material. The findings showed that mastery of the material was low, with 6 out of 20 students scoring below the minimum mastery criteria, mainly due to the use of conventional teaching methods. The research used a quasi-experimental design, specifically a One-Group Pretest-Posttest Design, involving 20 students selected through purposive sampling. Data were collected using pretest and posttest assessments with 20 items on the "Aku Peduli Lingkungan" material. The data analysis included validity and reliability tests, normality tests using Kolmogorov-Smirnov, and hypothesis testing using the Paired Sample T-Test. The results showed high validity (all items valid) and very high reliability (Cronbach’s Alpha = 0.912). The Paired Sample T-Test revealed a significant difference (p = 0.000 < 0.05), indicating that the scouting method significantly improved learning outcomes. Observations also showed positive development in independence and cooperation, with most students categorized as "Developing as Expected" (BSH) and "Very Developing" (SB). The study's management implications suggest that scouting-based activities can enhance learning and character development in educational settings.